Результаты поиска тяжелых нейтронных кластеров в делении ядер; Известия РАН. Серия физическая; Т. 72, № 3 - Варлачев (Варлачёв) В. А. Валерий Александрович; Гарапацкий А. А. Александр Александрович; Дудкин Г. Н. Геннадий Николаевич; Падалко В. Н. Владимир Николаевич; Скуридин В. С. Виктор Сергеевич; Солодовников Е. С. Евгений Семёнович; Чибисов Е. В. Евгений Владимирович (2008, 2008)
Заглавие с экрана